Redaktorzy "Zapisu" i "Pulsu" – pism literackich drugiego obiegu - Nolbrzak, Renata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
The article presents profiles of the main editors of the literary quarterly “Zapis” and “Puls” . Both magazines were printed in “samizdat” at the 70ties and 80ties of the last century. “Zapis" is warsaw literary periodical, which was editored by distinguished polish writers and poets including Jerzy Andrzejewski, Jacek Bocheński, Wiktor Woroszylski, Stanislaw Barańczak, Tadeusz Konwicki. “Puls” was editored by young literary men from Łódź directed by Jacek Bierezin, Witold Sułkowski and Tadeusz Walendowski. People involved in creating both magazines are not only creators and artists, but also activist of an anti-communist opposition. The article shows not only their art achivements, their role in creating and editing “Zapis” and “Puls” , but also influence of their literary output on fighting with the communist system in Poland.